Medical Devices Made of Substances: Possible Innovation and Opportunities for Complex Natural Products - Bilia, Anna Rita; Corazziari, Enrico Stefano; Govoni, Stefano; Mugelli, Alessandro; Racchi, Marco (Planta Medica, 2021)
The novel Regulation 2017/745/EC on medical devices introduces and strengthens the role of “medical devices made of substances”, which mostly include substances of natural origin. Natural products may follow different regulations, from food to therapeutics. Concerning their isolated constituents, extracts are characterized by a complexity that is not easily tackled from both a scientific and a regulatory point of view, but more importantly, from a therapeutic point of view. The evidence-based approach applied to isolated molecules requires appropriate evidence of quality, efficacy, and safety. The same needs must be reached for complex substances by finding appropriate methods to generate this evidence, and in addition, defining an appropriate regulatory field for them. From a scientific point of view, new methods, such as those proposed by systems biology, are available and applicable to complex substances. From a regulatory point of view, Directive 2001/83/EC on medicinal products seems to be modeled on single (or combinations of single) molecule products. On the other hand, Regulation 2017/745/EC on medical devices seems to apply to complex substances without derogating on quality, efficacy, and safety. The regulation specifically names and strengthens medical devices that include substances, mostly of natural origin, introducing the official term “medical devices made of substances”. This paper discusses and proposes an interpretation of important terms connected to this legislation, regarding both scientific and regulatory issues, and the opportunities the regulation may give for innovation and therapeutic improvement with natural complex substances.
Keywords: herbal medicinal products; medical devices; medical devices made of substances; Regulation 2017/745/EC; systems biology; pharmacological action